Modulation by neurotransmitters of catecholamine secretion from sympathetic ganglion neurons detected by amperometry - Koh, Duk-Su (The National Academy of Sciences of the USA, 1997)
Many neuromodulators inhibit N-type Ca(2+) currents via G protein-coupled pathways in acutely isolated superior cervical ganglion (SCG) neurons. Less is known about which neuromodulators affect release of norepinephrine (NE) at varicosities and terminals of these neurons. To address this question, we used carbon fiber amperometry to measure catecholamine secretion evoked by electrical stimulation at presumed sites of high terminal density in cultures of SCG neurons. The pharmacological properties of action potential-evoked NE release paralleled those of N-type Ca(2+) channels: Release was completely blocked by Cd(2+) or ω-conotoxin GVIA, reduced 50% by 10 μM NE or 62% by 2 μM UK-14,304, an α(2)-adrenergic agonist, and reduced 63% by 10 μM oxotremorine M (Oxo-M), a muscarinic agonist. Consistent with action at M(2) or M(4) receptor subtypes, Oxo-M could be antagonized by 10 μM muscarinic antagonists methoctramine and tropicamide but not by pirenzepine. After overnight incubation with pertussis toxin, inhibition by UK-14,304 and Oxo-M was much reduced. Other neuromodulators known to inhibit Ca(2+) channels in these cells, including adenosine, prostaglandin E(2), somatostatin, and secretin, also depressed secretion by 34–44%. In cultures treated with ω-conotoxin GVIA, secretion dependent on L-type Ca(2+) channels was evoked with long exposure to high K(+) Ringer’s solution. This secretion was not sensitive to UK-14,304 or Oxo-M. Evidently, many neuromodulators act on the secretory terminals of SCG neurons, and the depression of NE release at terminals closely parallels the membrane-delimited inhibition of N-type Ca(2+) currents in the soma.